2015
DOI: 10.1007/s13238-015-0223-8
|View full text |Cite
|
Sign up to set email alerts
|

MiR-33a suppresses breast cancer cell proliferation and metastasis by targeting ADAM9 and ROS1

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that have a pivotal role in the post-transcriptional regulation of gene expression by sequence-specifically targeting multiple mRNAs. Although miR-33a was recently reported to play an important role in lipid homeostasis, atherosclerosis, and hepatic fibrosis, the functions of miR-33a in tumor progression and metastasis are largely unknown. Here, we found that downregulated miR-33a in breast cancer tissues correlates with lymph node metastasis. MiR-33a expression is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 26 publications
2
68
0
Order By: Relevance
“…Wang et al (40) identified that miR-126 targeted ADAM9 to inhibit osteosarcoma proliferation and invasion. Zhang et al (41) reported that miR-33a repressed breast cancer cell growth and metastasis through the negative regulation of ADAM9. Further studies that explore additional novel targets for miR-154 and other miRNAs that can regulate ADAM9 in breast cancer will facilitate a complete understanding of the molecular mechanisms underlying the initiation and progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (40) identified that miR-126 targeted ADAM9 to inhibit osteosarcoma proliferation and invasion. Zhang et al (41) reported that miR-33a repressed breast cancer cell growth and metastasis through the negative regulation of ADAM9. Further studies that explore additional novel targets for miR-154 and other miRNAs that can regulate ADAM9 in breast cancer will facilitate a complete understanding of the molecular mechanisms underlying the initiation and progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-33a was recently identified as a tumor suppressor in melanoma, non-small cell lung cancer, and breast cancer by targeting multiple genes [22][23][24]. Here, we found that miR-33a could regulate CYR61 by binding to its 3'-UTR in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 77%
“…14 It has also been reported as an important tumor suppressor in distinct tumor types through deregulating its targets' expressions. 13,[15][16][17][18][19][20][21] Our investigation of a recent dataset, in which microRNAs in CD133-positive and CD133-negative cells 24 were profiled, demonstrated that miR-33a expression in CD133-positive cells, which were demonstrated to possess cancer stemlike features, 34 is significantly lower compared to corresponding CD133-negative cells, indicating a tumor suppressor function for miR-33a. Cancer stem cells, resembling normal stem cells in their biologic features, are thought to be an important component of tumors, leading to cancer initiation, development, recurrence, invasion, metastases, and therapy resistance.…”
Section: Discussionmentioning
confidence: 81%
“…The MiR‐33a is an intronic microRNA that resides within the 16 th intron of the SREBF2 gene with critical roles associated with regulation of lipid and cholesterol metabolism . It has also been reported as an important tumor suppressor in distinct tumor types through deregulating its targets' expressions . Our investigation of a recent dataset, in which microRNAs in CD133‐positive and CD133‐negative cells were profiled, demonstrated that miR‐33a expression in CD133‐positive cells, which were demonstrated to possess cancer stemlike features, is significantly lower compared to corresponding CD133‐negative cells, indicating a tumor suppressor function for miR‐33a.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation